Mineral Elements in Colocasia esculenta L. Schot and Soil Characteristics around a Major Construction Site in Otuoke, Bayelsa State, Nigeria - Etukudo, Mbosowo M.; Osim, Samuel E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2022)
Background: Mineral elements in Colocasia esculenta L. Schot and soil characteristics were examined around a major construction site in Otuoke, Bayelsa State, Nigeria. This study was conducted to examine the effects of construction activities on chemical properties of soil and mineral element contents of the test crop. Methods: The study area was sectioned into the construction site (S1 and S2) and the control site (S0). Plant materials and soil samples obtained from the three experimental locations were analyzed for mineral nutrients and physico-chemical characteristics, respectively, using standard procedures. Results: The results of this study revealed that the pH values of location 1-S1 and location 2-S2 were significantly lower than that of location 0 (S0)-control. The contents of organic matter, total nitrogen, available phosphorus, calcium and magnesium significantly (P< 0.05) increased with increase in distance from the construction site. The nitrogen, phosphorus, calcium and magnesium contents in C. esculenta significantly (P< 0.05) increased with increase in distance from the construction site. The potassium, copper, iron and lead contents in plant material decreased with increase in distance from the construction site. Conclusion: This study suggests that the construction activities have negative effects on the test crop (C. esculenta) due to the toxic pollutants usually generated from such operations. Therefore, toxic wastes generated during construction operations should be properly disposed without contamination to cultivated soils.